2017
DOI: 10.1097/dss.0000000000001091
|View full text |Cite|
|
Sign up to set email alerts
|

The Sterility of Partially Used Hyaluronic Acid Fillers After Long Storage

Abstract: Although it is commonly practiced, the storage of HA fillers after initial patient injection carries a real but small risk of contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…The remaining two microbiological studies that examined hyaluronic acid products showed growth of skin/oral flora in less than 15% of the samples . The main organism detected was S epidermidis followed by Corynebacterium species , Bacillus species , Staphylococcus oralis , and Diphtheroids . Immediate replacing needles used in injection with a sterile substitute before storage was associated with no growth in one study and growth in another study .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The remaining two microbiological studies that examined hyaluronic acid products showed growth of skin/oral flora in less than 15% of the samples . The main organism detected was S epidermidis followed by Corynebacterium species , Bacillus species , Staphylococcus oralis , and Diphtheroids . Immediate replacing needles used in injection with a sterile substitute before storage was associated with no growth in one study and growth in another study .…”
Section: Resultsmentioning
confidence: 94%
“… Four out of the six microbiological studies that examined hyaluronic acid products showed no growth, using aerobic, anaerobic, and/or fungal culture media . The remaining two microbiological studies that examined hyaluronic acid products showed growth of skin/oral flora in less than 15% of the samples . The main organism detected was S epidermidis followed by Corynebacterium species , Bacillus species , Staphylococcus oralis , and Diphtheroids .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations